2021
DOI: 10.1007/s12016-021-08878-x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Delayed Hypersensitivity Reactions to Antibiotics: Aminoglycosides, Clindamycin, Linezolid, and Metronidazole

Abstract: Hypersensitivity reactions including IgE-mediated and delayed cell-mediated reactions to aminoglycosides, clindamycin, linezolid, and metronidazole are rare. For aminoglycosides, allergic contact dermatitis is the most frequent reaction for which patch testing can be a useful step in evaluation. For clindamycin, delayed maculopapular exanthems are the most common reactions. There are case reports of clindamycin associated with drug rash with eosinophilia and systemic symptoms (DRESS), acute generalized exanthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 79 publications
0
13
0
1
Order By: Relevance
“…Immediate and delayed hypersensitivity reactions to clindamycin have been occasionally described, [3][4][5] but an FDE from clindamycin is considered very rare. 6 Although patch tests should be the first skin test to perform, the history in our case was not reliable enough to suspect an FDE at the initial assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate and delayed hypersensitivity reactions to clindamycin have been occasionally described, [3][4][5] but an FDE from clindamycin is considered very rare. 6 Although patch tests should be the first skin test to perform, the history in our case was not reliable enough to suspect an FDE at the initial assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Given the structural similarity between clindamycin and lincomycin (the former having a chlorine atom instead of an hydroxyl group) cross‐reactivity between these drugs might be anticipated; however, we have shown that this does not necessarily occur. Although the patch test to lincomycin was negative, false‐negative patch tests readily occur, 5 and so an OCT was additionally performed, allowing us to demonstrate the effective tolerance to lincomycin. The patient has thus been recommended to avoid clindamycin, but not lincomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Metronidazole is an antibacterial compound belonging to the class of imidazoles, a subgroup of nitroimidazoles, which acts against a wide variety of microorganisms [ 15 ]. It is clinically effective in the treatment of periodontitis and peri-implantitis caused by anaerobic bacteria [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is clinically effective in the treatment of periodontitis and peri-implantitis caused by anaerobic bacteria [ 16 ]. It presents a good therapeutic response, but its high toxicity after continuous systemic doses can, for example, manifest gastrointestinal disorders, dizziness, and headaches, among others, often causing the patient to discontinue treatment [ 15 ]. Thus, the local delivery of metronidazole could reduce the systemic toxicity of the antibiotic and increase its efficiency even with lower doses.…”
Section: Introductionmentioning
confidence: 99%
“…It is clinically effective in the treatment of periodontitis and peri-implantitis caused by anaerobic bacteria [12]. It presents a good therapeutic response, but its high toxicity after continuous systemic doses can, for example, manifest gastrointestinal disorders, dizziness, headaches, among others, often causing the patient to discontinue treatment [13]. Thus, a local delivery of metronidazole could reduce the systemic toxicity of the antibiotic and increase its efficiency even with lower dose.…”
Section: Introductionmentioning
confidence: 99%